Correlation between Blood Glucose Level and Short-Term Memory Score among 4th and 5th Grades of Primary School Children in Bogor, Indonesia - Al Khairiyah, Hanifah; Hardinsyah, Hardinsyah; Dewi, Mira Dewi (Jurnal Gizi dan Pangan, 2022)
The study aimed to analyze the correlation between Blood Glucose levels (BG) and Short-Term Memory scores (STM) among primary school children in Bogor, as controlled by Socioeconomic Status (SES), BMI-for-age (BAZ), Hemoglobin (Hb), folate, and vitamin B12 levels. It was a cross-sectional study applied for 915 students of the 4th–5th grades from 16 primary schools in the suburban area of the Cijeruk district. Morning blood samples were drawn from venous puncture of the inner arm. The specimens were then transported to laboratories to analyze the BG (hexokinase methods), Hb (non-cyanide Hb), as well as folate, and vitamin B12 using Liquid Chromatography and Mass Spectrometry. The STM was obtained through an object recall test performed by trained psychologists. The actual body weight and height were measured to determine BAZ. The characteristics of subjects and their SES were collected through interviews and structured questionnaires. Mann-Whitney and Chi-square tests were performed to compare differences between variables that were grouped by genders. Correlations between predictors and predicted variables were analyzed using simple logistic regression for the bivariates analysis and a binary logistic regression test for the multivariate analysis. There were significant differences in BAZ, BG, and STM between boys and girls (p<0.05). Most of the subject's BAZ was normal (85.2%). About 50.9% of subjects had normal Hb, 99.8% had folate deficiency, 47.8% had normal vitamin B12 level, and 54.9% had good STM score. There was no significant correlation between BAZ, Hb, folate, and vitamin B12 level with STM (p≥0.05), respectively. There was a significant positive correlation between BG and STM (p<0.05; OR=1.583; 95% CI:1.067−2.348) after being controlled by BAZ, subject’s characteristic, and SES. In conclusion, optimum blood glucose level improved the STM in primary school children. Therefore, provision of balanced diet, more especially breakfast, for school children is highly important.